PENGARUH AMBIGUITAS PERAN TERHADAP KINERJA INDIVIDU: STRES KERJA SEBAGAI MEDIASI - Natasya, Fathya Jihan; Pujianto, Wahyu Eko (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
The purpose of this research is to analyze the influence of role ambiguity on individual performance, analyze the influence of role ambiguity on job stress, analyze the influence of job stress on individual performance, analyze role ambiguity on individual performance through job stress. This research uses quantitative methods with a population of employees of the Sidoarjo Indonesian Electrical and Mechanical Contractors Association. The sample used was all employees, totaling 47 respondents. Data was collected using an online questionnaire with Google Form for approximately one month. This research analysis uses Partial Least Square (PLS) SmartPLS 4.0 software. The results of this study found that (1) Role ambiguity has a positive and significant influence on individual performance (2) Role ambiguity has a positive but not significant influence on job stress (3) Job stress has a negative and insignificant influence on individual performance (4) role ambiguity has no effect on individual performance through job stress has a negative influence.